2012
DOI: 10.1128/jcm.05175-11
|View full text |Cite
|
Sign up to set email alerts
|

Is Hepatitis C Virus Core Antigen an Adequate Marker for Community Screening?

Abstract: A new hepatitis C virus (HCV) core antigen (HCV Ag) assay was thought to have a good correlation with HCV RNA. The aim was to elucidate the usefulness of this HCV Ag assay in community screening. In a township where HCV is endemic, 405 residents aged 58 years or older responded to a follow-up community screening. All subjects were tested for anti-HCV (AxSYM, version 3.0; Abbott Diagnostics) and HCV Ag (Architect HCV Ag test; Abbott Diagnostics). For subjects with anti-HCV signal-to-cutoff ratios (S/CO) > 10 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 25 publications
2
38
2
Order By: Relevance
“…Several other studies using HCVcAg testing reported a significant correlation between serum levels of HCV-RNA and HCVcAg with different linear regression coefficients ranging from 0.6 to 0.8 (22,24,36,30−33), which is higher than seen in our study. In addition, the weak correlation reported in our study is lower than that reported elsewhere among those infected with HCV genotype 4 or other genotypes (9)(10)(11)34,35). This could be attributed to viral genetic differences and/or patient characteristics.…”
Section: Discussioncontrasting
confidence: 55%
“…Several other studies using HCVcAg testing reported a significant correlation between serum levels of HCV-RNA and HCVcAg with different linear regression coefficients ranging from 0.6 to 0.8 (22,24,36,30−33), which is higher than seen in our study. In addition, the weak correlation reported in our study is lower than that reported elsewhere among those infected with HCV genotype 4 or other genotypes (9)(10)(11)34,35). This could be attributed to viral genetic differences and/or patient characteristics.…”
Section: Discussioncontrasting
confidence: 55%
“…However, the sensitivity of the Abbott Architect HCVcAg assay was only 64.7%‐81.9% when serum HCV RNA was <4 log IU/mL and 0.0%‐19.7% when serum HCV RNA was <3 log IU/mL . Furthermore, a high false‐positive rate occurred in patients with R‐HCV infection (i.e., negative HCV RNA and positive anti‐HCV results) when tested with the current HCVcAg assay …”
mentioning
confidence: 92%
“…A number of studies have demonstrated good correlation between HCVcAg and HCV RNA levels, particularly in HCV-monoinfected individuals [6,7,8,9,10,11,12,13]. As a result, HCVcAg testing is considered to be an alternative assay to conventional HCV RNA quantification with the advantages of rapidity, reproducibility and feasibility in settings with limited resources [14]. To date, data regarding the correlation between HCVcAg and HCV RNA levels in patients coinfected with HIV are still limited [15,16,17].…”
Section: Introductionmentioning
confidence: 99%